1998
DOI: 10.1046/j.1365-313x.1998.00317.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered plastidic ATP/ADP‐transporter activity influences potato (Solanum tuberosumL.) tuber morphology, yield and composition of tuber starch

Abstract: SummaryThe metabolic function of the plastidic ATP/ADP transporter (AATP) in heterotrophic plastids was examined in transgenic potato plants that exhibited increased or decreased amounts of the protein. Altered mRNA levels correlated with activities of the plastidic ATP/ADP transporter. Potato tubers with decreased plastidic ATP/ADP transporter activities exhibited reduced starch contents whereas sense lines accumulated increased amounts of tuber starch. Starch from wild-type tubers had an amylose content of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
195
2
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(209 citation statements)
references
References 40 publications
11
195
2
1
Order By: Relevance
“…In AATP1(St) overexpressing (sense) plants exhibiting increased transporter activity, the level of tuber starch was enhanced. In tubers of AATP1(St) antisense plants, which display decreased transporter activity, the level of starch was conversely reduced by about 50% compared with the wild type (Tjaden et al, 1998). The metabolic alterations in AATP1(St) sense and antisense tubers were not limited to the level of starch but also influenced soluble metabolites.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…In AATP1(St) overexpressing (sense) plants exhibiting increased transporter activity, the level of tuber starch was enhanced. In tubers of AATP1(St) antisense plants, which display decreased transporter activity, the level of starch was conversely reduced by about 50% compared with the wild type (Tjaden et al, 1998). The metabolic alterations in AATP1(St) sense and antisense tubers were not limited to the level of starch but also influenced soluble metabolites.…”
mentioning
confidence: 88%
“…To determine whether there are differences in the capacity to produce extracellular H 2 O 2 between transgenic AATP1(St) and wild-type potato tuber tissue, the release of H 2 O 2 from these two types of tissue was quantified. We first focused on tissues from wildtype and antisense line JT654 plants, because tubers from the latter show strong inhibition of starch biosynthesis and substantially altered levels of primary metabolites (Tjaden et al, 1998;Geigenberger et al, 2001).…”
Section: Aatp1(st) Antisense Potato Tubers Exhibit Potentiated H 2 O mentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive review of these strategies alongside application of the framework of metabolic control analyses revealed that a considerable portion of the control of starch biosynthesis in this organ resided in the reaction catalyzed by AGPase (Geigenberger et al, 2004). In addition, considerable control has been demonstrated to be harbored by the plastidial adenylate and Glc-6-P transporter (Tjaden et al, 1998;Zhang et al, 2008), with a minor yet considerable proportion also vested in the plastidial phosphoglucomutase reaction . Studies beyond the direct pathway of starch biosynthesis also indicate important roles for the mitochondrial NADmalic enzyme (Jenner et al, 2001) and the plastidial adenylate kinase (Regierer et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Of these reactions, although some of the control of starch synthesis resides in the plastidial phosphoglucomutase reaction (Fernie et al, 2001b), the AGPase reaction harbors the highest proportion of control within the linear pathway (Sweetlove et al, 1999;Geigenberger et al, 1999Geigenberger et al, , 2004. In addition, considerable control resides in both the Glc-6-P phosphate antiporter (Zhang et al, 2008) and the amyloplastidial adenylate transporter (Tjaden et al, 1998;Zhang et al, 2008) as well as in reactions external to the pathways, such as the amyloplastidial adenylate kinase (Regierer et al, 2002), cytosolic UMP synthase (Geigenberger et al, 2005), and mitochondrial NAD-malic enzyme (Jenner et al, 2001).…”
mentioning
confidence: 99%